Corticofugal GABAergic projection neurons in the mouse frontal cortex - Tomioka, Ryohei; Sakimura, Kenji; Yanagawa, Yuchio (Frontiers in Neuroanatomy, 2015)
Cortical projection neurons are classified by hodology in corticocortical, commissural and corticofugal subtypes. Although cortical projection neurons had been regarded as only glutamatergic neurons, recently corticocortical GABAergic projection neurons has been also reported in several species. Here we demonstrate corticofugal GABAergic projection neurons in the mouse frontal cortex. We employed viral-vector-mediated anterograde tracing, classical retrograde tracing, and immunohistochemistry to characterize neocortical GABAergic projection neurons. Injections of the Cre-dependent adeno-associated virus into glutamate decarboxylase 67-Cre knock-in mice revealed neocortical GABAergic projections widely to the forebrain, including the cerebral cortices, caudate putamen, ventral pallidum, lateral globus pallidus, nucleus accumbens, and olfactory tubercle. Minor GABAergic projections were also found in the mediodorsal thalamic nucleus, diagonal band of Broca, medial globus pallidus, substantial nigra, and dorsal raphe nucleus. Retrograde tracing studies also demonstrated corticofugal GABAergic projection neurons in the mouse frontal cortex. Further immunohistochemical screening with neurochemical markers revealed the majority of corticostriatal GABAergic projection neurons were positive for somatostatin-immunoreactivity. In contrast, corticothalamic GABAergic projection neurons were not identified by representative neurochemical markers for GABAergic neurons. These findings suggest that corticofugal GABAergic projection neurons are heterogeneous in terms of their neurochemical properties and target nuclei, and provide axonal innervations mainly to the nuclei in the basal ganglia.